Aptamer-engaged nanotherapeutics against SARS-CoV-2 - Jing Zhang; Dan Wang; Chiu Kwok; Liujun Xu; Michalina Famulok (Discover Nano)
Abstract The COVID-19 pandemic, caused by the virus SARS-CoV-2 infection, has underscored the critical importance of rapid and accurate therapeutics. The neutralization of SARS-CoV-2 is paramount in controlling the spread and impact of COVID-19. In this context, the integration of aptamers and aptamer-related nanotherapeutics presents a valuable and scientifically significant approach. Despite the potential, current reviews in this area are often not comprehensive and specific enough to encapsulate the full scope of therapeutic principles, strategies, advancements, and challenges. This review aims to fill that gap by providing an in-depth examination of the role of aptamers and their related molecular medicine in COVID-19 therapeutics. We first introduce the unique properties, selection, and recognition mechanism of aptamers to bind with high affinity to various targets. Next, we delve into the therapeutic potential of aptamers, focusing on their ability to inhibit viral entry and replication, as well as modulate the host immune response. The integration of aptamers with nucleic acid nanomedicine is explored. Finally, we address the challenges and future perspectives of aptamer and nucleic acid nanomedicine in COVID-19 therapeutics, including issues of stability, delivery, and manufacturing scalability. We conclude by underscoring the importance of continued research and development in this field to meet the ongoing challenges posed by COVID-19 and potential future pandemics. Our review will be a valuable resource for researchers and clinicians interested in the latest developments at the intersection of molecular biology, nanotechnology, and infectious disease management.